Effects of Co γ Irradiation on the Reproductive Function of - Fengmei Cui; Nan Ma; Xiaojing Han; Na chen; Yue Xi; Weiye Yuan; Yufan Xu; Jianfang Han; Xiaoyan Xu; Yu Tu (SAGE Publishing, 2019)
The effects of ionizing radiation on the reproductive system have always been a matter of great interest. Both artificial and naturally occurring ionizing radiation can directly or indirectly affect the reproductive system via the introduction of DNA single-strand and double-strand breaks, the excitation of water molecules, and the generation of free radicals. In order to quantitatively investigate the effects of ionizing radiation on reproductive function, 60 Co γ irradiation was applied on a model organism, Caenorhabditis elegans (C. elegans) . The egg-laying and embryo-hatching activities were observed for the parent (F0) and the first 2 progeny (F1 and F2) generations. The incidence rate of ovipositor malformation was also recorded. Acridine orange was used to detect the number of apoptotic germ cells. With the above metrics, the effects of 60 Co γ irradiation on the reproductive function of C. elegans were systematically evaluated. The results showed that the postirradiation egg-laying and embryo-hatching activities of the F0 generation were increasingly suppressed by increasing doses of 60 Co γ irradiation. Those of the F1 generation showed a trend toward recovery although also suppressed by the radiation to the F0 generation compared with the control. Those activities were restored to normal or near-normal levels for the F2 generation. The incidence rate of ovipositor malformation was greatly increased by 60 Co γ irradiation according to radiation doses. Gamma irradiation by 60 Co also substantially induced germ cell apoptosis, and the apoptosis rate increased with increasing radiation doses. Therefore, 60 Co γ irradiation affects the reproductive function of C. elegans . The suppression on its reproductive function increases with increasing radiation doses. The reproductive functions of progeny generations are also affected and weakened.